Seed-free short time synthesis of zincosilicate zeolite VPI-8 and its catalysis of methane dehydroaromatization reaction - Huang, Chaoran (Kansas State University, 2018)
Zeolite refers to a microporous material, which is also called a molecular sieve. There are three major industrial applications of zeolites: adsorbents, ion exchangers, and catalysts; and many other minor applications including: sensors, agriculture, medicine, veterinary, hydrogen storage, fuel cells, microreactors, membrane reactors, and racemic separations. Today, zeolite is not limited to aluminosilicate. Researchers are attempting to use other species (such as B, Ga, Ge, Ti, and Zn) to replace aluminum in zeolites framework to accomplish particular applications. In 1991, the first zincosilicate zeolite was synthesized by Annen et al.. Currently, only four zincosilicate zeolites have been synthesized. Theoretically, zincosilicate should balance divalent cations better than aluminosilicate zeolites to provide a stronger acid site especially for hydrogen cracking reactions. Large pore VET type VPI-8 (Li₁.₉₁₄Zn₁.₉₁₄Si₁₅.₀₈₆O₃₄) is the most thermal stable of all the zincosilicate zeolites and has low chemicals cost, however, a high crystallinity VPI-8 required prohibitively long synthesis times or seeded synthesis procedures. In this work, a seed-free short time synthesis zincosilicate zeolite VPI-8 is presented. Methane, also known as natural gas, had become the largest abundant carbon reserve today, more than the amount of the fossil fuel including conventional gas, oil, and coal. Unlike fossil fuel, methane can be recycled from landfill. Methane could be used to produce useful and/or expensive chemicals via syngas conversion to fuel, paraffin, methanol, alcohol, and dimethoxyethane. In addition to pathways via a syngas intermediate, methane could react directly to ethylene, formaldehyde, and aromatics. Because syngas preparation and compression usually expends 60-70% of the capital cost and consumes almost all the energy of operation, more and more researchers are exploring direct methane activation. However, the high stability of methane is one of the limitations, and coking is another limitation. In this work, methane dehydroaromatization (MDA) over zincosilicate zeolite Li-VPI-8 and ion exchanged Ni/Li-VPI-8 are investigated, due to the stronger acid site in zincosilicate than aluminosilicate zeolites. This is the first time to study using zincosilicate as catalyst, capitalizing on the more efficient synthesis methods demonstrated in this work.
Keywords: zeolite; VPI-8; zincosilicate; synthesis; dehydroaromatization